1989
DOI: 10.1111/1523-1747.ep13075079
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Structure and Function: Perspectives on Morphologic Approaches to the Study of the Granular Layer Keratinocyte.

Abstract: S tephen Rothman [1] wrote: "Modern dermatology has been built on the solid pillars of precise macro-and microscopic observation, accurate recording and meaningful interpretation ofthe findings. No natural science can exist without direct observation of natural phenomena, and dermatology has become a great discipline because we have had so many good observers." He went on to state further that "... whereas the immense knowledge acquired by the classical descriptive methods is still rapidly increasing, the appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 165 publications
5
36
1
Order By: Relevance
“…Thickening was systematically observed in at least thirty animals, with skin from dierent places, including the back, the head, the tail and the abdomen. Within the epidermis, the granular layer was noticeably dierent, consisting of more cell layers with granules but with less granules per cell than normal skin ( Figure 4a, see arrows) (Holbrook, 1989). There was no evidence of enlarged cells with giant nuclei or multinucleated cells (Lundgren et al, 1997).…”
Section: The Epidermis Of Transgenic Animals Is Thicker and Has Altermentioning
confidence: 97%
“…Thickening was systematically observed in at least thirty animals, with skin from dierent places, including the back, the head, the tail and the abdomen. Within the epidermis, the granular layer was noticeably dierent, consisting of more cell layers with granules but with less granules per cell than normal skin ( Figure 4a, see arrows) (Holbrook, 1989). There was no evidence of enlarged cells with giant nuclei or multinucleated cells (Lundgren et al, 1997).…”
Section: The Epidermis Of Transgenic Animals Is Thicker and Has Altermentioning
confidence: 97%
“…The softness of the mammalian epidermis has been related to the evolution of a granular layer containing keratohyaline granules that allow the production of a pliable stratum corneum (Spearman 1964;Maderson 2003). In the epidermis of mouse, keratinocytes of the stratum granulosum contain keratohyaline granules that are distinguished into irregularly shaped F-granules, L-granules, and composite granules (Holbrook 1989;Steven et al 1990;Resing & Dale 1991;Dale et al 1994;Hardman et al 1998). However, the above morphology for keratohyalin granules is not common in the epidermis of other mammalian species, especially for L-granules, typically present in the mouse epidermis but that are *Correspondence: Dipartimento di Biologia evoluzionistica sperimentale, University of Bologna, via Selmi 3, 40126 Bologna, Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Fax: +39 051 209 4286. Email: alibardi@biblio.cib.unibo.it often absent in other species, namely humans, rat and platypus (Holbrook 1989;Steven et al 1990;Yoneda et al 1992;Alibardi 2009Alibardi , 2010.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that a pool of preformed IL-1 existed herein that was subsequently localized by immunohistochemical and immunoclectron microscopy to distinct stages in the differentiation program of the epidermis [6]. Differentia tion of the kératinocytes is a complex process which in cludes several stages from a stem cell population |7] to a 1 This work was supported in part by grants from the Fonds National Suisse pour la Recherche Scientifique (3. fully anuclcated cell [8]; in this respect the process has been compared to that of the red blood cells lineage. It is interesting in this context that IL-1 is now known as being identical to hemopoietin I.a factor that enhances the pro duction of hemopoietic progenitor cells from stem cells and their subsequent proliferation in response to colony stimulating factor [1,2].…”
Section: Introductionmentioning
confidence: 99%